2019
DOI: 10.1111/aec.12770
|View full text |Cite
|
Sign up to set email alerts
|

Fire resilience of a rare, freshwater crustacean in a fire‐prone ecosystem and the implications for fire management

Abstract: Understanding species’ responses to fire regimes, particularly rare or threatened species, is important for land managers tasked with managing for biodiversity. Hickman's Allanaspides (Allanaspides hickmani, Anaspidesidae) is a rare, primitive, shrimp‐like crustacean, with high conservation value. It is restricted to a single catchment in the island state of Tasmania, Australia, where it occurs within moorland pools typically containing crayfish (Ombrastacoides spp.) burrows. Although its moorland habitat has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Even if temporary elevation of water temperatures can be avoided by retreat into deep burrows, subsequent exposure to toxins released by burning, eutrophication and anoxia caused by excessive organic deposition and runoff can nevertheless be detrimental (New, 2014;Emelko et al, 2016;Harper et al, 2019). Although some aquatic crustaceans have demonstrated resilience to habitat burning (Driessen, 2019), little is known about fire resilience of crayfishes, such as Euastacus, which typically favour cool, well-oxygenated, oligotrophic waters. In addition, species of Euastacus regularly leave the stream to forage.…”
Section: Spiny Freshwater Crayfishesmentioning
confidence: 99%
“…Even if temporary elevation of water temperatures can be avoided by retreat into deep burrows, subsequent exposure to toxins released by burning, eutrophication and anoxia caused by excessive organic deposition and runoff can nevertheless be detrimental (New, 2014;Emelko et al, 2016;Harper et al, 2019). Although some aquatic crustaceans have demonstrated resilience to habitat burning (Driessen, 2019), little is known about fire resilience of crayfishes, such as Euastacus, which typically favour cool, well-oxygenated, oligotrophic waters. In addition, species of Euastacus regularly leave the stream to forage.…”
Section: Spiny Freshwater Crayfishesmentioning
confidence: 99%
“…Ectothermic species tolerate thermal increases up to an upper limit, defined as the critical thermal maximum, after which further increases in temperature are lethal (Pörtner & Peck, 2010). Although the localized mortality of aquatic organisms is often reported following major wildfire events (Burton, 2005;Driessen, 2019;Johnston et al, 2014;Silva et al, 2020), this review found no evidence of direct mortality of aquatic fauna attributable to extreme water temperatures caused by wildfires. However, periods of warming during and after a fire could result in local extirpation of species if species-specific thermal limits are surpassed.…”
Section: Water Temperaturementioning
confidence: 80%
“…The overall status of the plant community reflects the ecological background of a country, and is an important basis for ecological restoration, ecological construction, and the formulation of land use policy. Plant communities (i.e., the collection of plants living in a specific area) possess differences in ecological resistance and resilience to droughts [10,11], other types of short-term climatic anomalies [12][13][14], as well as local disturbances, including a lack of resources [15,16], species invasions [15], or fire [17]. Different plant communities have different species compositions and community structures.…”
Section: Introductionmentioning
confidence: 99%